Famine in Africa: causes, responses, and prevention - von Braun, Joachim; Teklu, Tesfaye; Webb, Patrick (International Food Policy Research Institute, 1999)
While acute famines may appear to be similar across continents, their causes, their victims, and the policies needed to respond effectively to famines differ immensely. The authors seek to fill in empirical and conceptual gaps that continue to hinder analysis of famines in Africa. They present analyses from detailed studies of country policies as they affect markets, communities, and households in the context of famine.